BIOPLASTIC CONTRIBUTION IN THE PLASTICS INDUSTRY AND ITS ECONOMIC DEVELOPMENT (International Journal of Food and Nutritional Sciences, 2022)
Leo Baekeland American - Belgium chemist, formulated and synthesized Bakelite, it had been considered the gift to the society and solution to the many problems. But later on, overuse, imprudent use of the plastics material created the turmoil on the blue planet thereby creating environmental pollution deteriorating the balance of atmosphere. A micro plastic becomes the major threat to the soil contamination, pollution. Over the period of time demand of plastics materials is increasing because of growing population and increased standard of living. Therefore, there has been tremendous research work is in process to generate material i.e., bioplastic which would be appropriately substitute to the present crude oil-based conventional plastics material. Bioplastic have been accepted worldwide because bioplastic is generally environmental; friendly, harmless materials and ultimately in all aspects it has become the need of the time. National governments, policy makers are supporting bioplastic material. This paper reveals the role of bioplastic in the market thereby its economical contribution in the plastic industries. In the world, bioplastic contribution was estimated USD 11.2 billion in 2021 and is increasing gradually will reach around USD 46.1 billion by 2030, CAGR registered of about 17.2% between 2022 to 2030.